Dried tomato pomace supplementation to reduce lamb concentrate intake: Effects on growth performance and meat quality. (November 2018) - Valenti, Bernardo; Luciano, Giuseppe; Pauselli, Mariano; Mattioli, Simona; Biondi, Luisa; Priolo, Alessandro; Natalello, Antonio; Morbidini, Luciano; Lanza, Massimiliano
Abstract: The effect of dried tomato pomace (DTP) was tested on lamb performances, meat fatty acids and oxidative stability. For 36 days, one group of lambs ( n  = 7; CON) was fed a commercial concentrate, while the other group ( n  = 7; DTP) received DTP in addition to CON diet. The administration of DTP reduced ( P  < .05) concentrate intake, with no effect on animal performances. The DTP treatment tended to increase total polyunsaturated fatty acids (PUFA; P  = .075), PUFA n -6 ( P  = .071), α-linolenic acid ( P  = .096) and increased linoleic acid ( P  < .05), γ-tocopherol ( P  < .001) and retinol ( P  < .001) in meat. In raw meat, DTP treatment increased L* ( P  = .059), b* ( P  < .05), C* ( P  = .052) and H* ( P  < .05) values compared to CON, while lipid oxidation was not affected. In meat homogenates incubated with pro-oxidants, DTP tended to reduce 2-thiobarbituric acid reactive substances (TBARS; P  = .088). Therefore, DTP supplementation decreased the consumption of commercial concentrate without detrimental effects on animal performances and meat quality traits.